The network always wins : how to survive in the age of uncertainty - Hinssen, Peter, ....- (Gent : Across technology, 2014)
Perhaps the strangest thing about networks is that they grow without a grand design. In that respect they're much more organic than any structure we deliberately create in our organizations. The Internet-the network that has transformed our lives and society was created not to execute a strategic blueprint but simply to grow. The network on which we have become dependent on to communicate, to receive news, to work and shop and bank and book holidays, was never deigned to help us do any of those things. It wasn't eve designed, period. It just gres. That fact can be vexing to technologists seeking to create logical sustems that bring control and cerainty to an increasingly colatile world. But those who cling to this nostalgic goal are dooed to fail. In the age of uncertainty, the best hope for organizations is to learn how networks operate so that they can become more like networks themselves. Their future-like ours-depends on it.
Keywords: Netwerken